Technological factors of the process of soil compaction in complex construction conditions - Umanets, I.; Basarab, V. (Ways to Improve Construction Efficiency, 2024)
The article is devoted to the technology of mechanical soil compaction in difficult construction site conditions. The compaction of the soil occurs due to certain force loads on the soil. The actuality of the soil compaction process, which ultimately determines the quality of construction product, was emphasized. The basic physical and mechanical properties of soil and technological parameters of the compaction process were given. Attention is focused on the fact that the choice of soil compaction technology in difficult conditions is based on the understanding of the fact that it is necessary to consider the compaction process as a complex model of the interaction of the compaction machine with the base soil. It is noted that the choice of the mode of static or dynamic action on the base soil depends on the correct choice of the mathematical model of the machine-soil interaction system. An overview of the existing methods of soil compaction was conducted and the feasibility of researching methods of soil compaction in difficult construction conditions was substantiated in order to select the optimal set of compaction equipment. An analysis of existing soil compaction technologies was carried out with the aim of determining the optimal technological parameters of the soil compaction process in difficult construction conditions. The technological scheme of the soil compaction process in difficult conditions was given. The technology of the works is described, taking into account the properties of the soil, the method of compaction, the parameters of the compaction equipment, as well as the conditions of the works. The main technological parameters of the soil compaction process are proposed - the thickness of the compacted soil layer, the number of passes of the compaction machine, as well as the speed of its movement. A theoretical-experimental method of finding the optimal parameters of the interaction of the compaction machine with the base soil is proposed in order to establish the optimal limits of the varied parameters of the technological process of soil compaction in complex construction conditions. An analysis of structural and technological parameters of compacting machines was carried out with the aim of effective use in the conditions of construction production. Basic recommendations for choosing a compaction method and a set of compacting equipment were given, depending on the type of soil and conditions of work.